2010
DOI: 10.1103/physrevlett.104.125001
|View full text |Cite
|
Sign up to set email alerts
|

Planar Wire-ArrayZ-Pinch Implosion Dynamics and X-Ray Scaling at Multiple-MA Drive Currents for a Compact Multisource Hohlraum Configuration

Abstract: An indirect drive configuration is proposed wherein multiple compact Z-pinch x-ray sources surround a secondary hohlraum. Planar compact wire arrays allow reduced primary hohlraum surface area compared to cylindrical loads. Implosions of planar arrays are studied at up to 15 TW x-ray power on Saturn with radiated yields exceeding the calculated kinetic energy, suggesting other heating paths. X-ray power and yield scaling studied from 1-6 MA motivates viewfactor modeling of four 6-MA planar arrays producing 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…However, pulsed power offers much more efficient energy coupling than lasers. Here, we report on the first proof-of-the principal experimental demonstration of the full configuration of new compact hohlraum design with a central target and tailored shine shields at UNR's 1.7 MA Zebra generator, as jointly proposed by the Sandia National Laboratories and the University of Nevada, Reno [1]. This was the joint success of two independent lines of multi-year research efforts.…”
Section: Introductionmentioning
confidence: 99%
“…However, pulsed power offers much more efficient energy coupling than lasers. Here, we report on the first proof-of-the principal experimental demonstration of the full configuration of new compact hohlraum design with a central target and tailored shine shields at UNR's 1.7 MA Zebra generator, as jointly proposed by the Sandia National Laboratories and the University of Nevada, Reno [1]. This was the joint success of two independent lines of multi-year research efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these remarkable achievements the search for new, more effective wire array load configurations continues [5]. This search has inspired several extensive programs for studying the wire array implosion at 1 MA currents at the university based laboratories, first at the Imperial College in UK [6,7] and later at the University of Nevada, Reno (UNR) [8][9][10][11] and Cornell University (see, for example, Ref.…”
mentioning
confidence: 99%
“…Since that time numerous experiments have demonstrated that among all the other low-wirenumber loads the planar wire arrays yield the highest x-ray radiation energies and powers [9][10][11]. Two years later, the single planar array loads have been successfully tested at 3 − 5 MA currents on Saturn generator at SNL [5,13,14]. By now, several novel applications of planar wire arrays have been proposed and tested at UNR, such as the new hohlraum design for ICF-related experiments [5], the possibility of controlling the shape of the x-ray radiation pulse [15], the experiments with multi-planar arrays related to the laboratory astrophysics [16], and skewed wire double planar array configurations with induced axial magnetic field [17].…”
mentioning
confidence: 99%
See 2 more Smart Citations